Assessing transformational change potential: the case of the Tunisian cement Nationally Appropriate Mitigation Action (NAMA). (3rd July 2018) - Boodoo, Zyaad; Olsen, Karen Holm
ABSTRACT: To effectively address the root causes of carbon lock-in across developing countries, Nationally Appropriate Mitigation Actions (NAMAs) with transformational change characteristics are being supported by donors and finance mechanisms as a means to achieve ambitious nationally determined contributions (NDCs). However, there is still a scarcity of empirical studies on how transformational change policies and actions are designed and supported in practice. This article addresses such a gap in knowledge by combining theoretical insights from the multi-level perspective and transitions management literature to examine a donor-supported cement sector NAMA in Tunisia developed during 2012–2013. A narrative is constructed to analyse the adequacy of the NAMA design to promote structural shifts towards low carbon development in the cement sector. Data collection is based on semi-structured interviews and documentation gathered during field work in Tunisia 2014–2015. The study finds that the NAMA design is not likely to lead to transformational change of the cement sector, since underlying factors accounting for lock-in are not properly tackled. Although the NAMA has enabled new and promising sectoral partnerships across the cement sector, the analysis suggests that the NAMA's transformational potential is currently limited by a number of factors not being adequately addressed. Measures are proposed to reorient the NAMA towards promoting system innovation, building on further research and experimentation with the policy entrepreneurial role of donors. Key policy insights Underlying factors such as the absence of local finance institutions and the lack of reflexivity features in project design restrict the potential of the Tunisian cement NAMA to spur transformation to low carbon development. To tackle underlying causes of carbon lock-in and reorient policies and actions for transformational design, the promotion of feedback loops and self-contemplation needs to be based on a long-term vision, experimentation, social learning and information gathered during implementation. Donors need to re-think their existing modalities to better support unpredictable and highly political changes for sustainability transitions in developing countries.